Final Project and Minithesis on Economics Topics: Problems and Solution - Widiastini, Ni Made Ary (LPPM Undiksha, 2018)
This paper tries to describe problems faced by students in general in writing final project or minithesis on Economics topics. As the last requirement every student at the Sarjana and Diploma levels, final project or minithesis is often a new and difficult problem faced by the students as they enter the last semester. In some cases, the students besides being late to graduate also drop out because they do not finish the final project or minithesis at the end of the study program. One of the factors that cause this is the studensâ failure to understand what to be chosen as a problem, to formulate the problem, or to find an appropriate title for the problem, so that the solution to the problem has been formulated. In this paper is described the technique to understand something which is appropriate to be made a title for a final project or minithesis, then how to formulate problems, to select a method of study which is suitable for the problem investigated, the data collection technique and data analysis. Through this paper it is expected that the students at the Sarjana and Diploma levels can understand how to write a final project or thesis in a simple away.